Muscular Dystrophies at Different Ages: Metabolic and Endocrine Alterations - Oriana del Rocío Cruz Guzmán; Ana Laura Chávez García; Maricela Rodríguez-Cruz (International Journal of Endocrinology)
Common metabolic and endocrine alterations exist across a wide range of muscular dystrophies. Skeletal muscle plays an important role in glucose metabolism and is a major participant in different signaling pathways. Therefore, its damage may lead to different metabolic disruptions. Two of the most important metabolic alterations in muscular dystrophies may be insulin resistance and obesity. However, only insulin resistance has been demonstrated in myotonic dystrophy. In addition, endocrine disturbances such as hypogonadism, low levels of testosterone, and growth hormone have been reported. This eventually will result in consequences such as growth failure and delayed puberty in the case of childhood dystrophies. Other consequences may be reduced male fertility, reduced spermatogenesis, and oligospermia, both in childhood as well as in adult muscular dystrophies. These facts all suggest that there is a need for better comprehension of metabolic and endocrine implications for muscular dystrophies with the purpose of developing improved clinical treatments and/or improvements in the quality of life of patients with dystrophy. Therefore, the aim of this paper is to describe the current knowledge about of metabolic and endocrine alterations in diverse types of dystrophinopathies, which will be divided into two groups: childhood and adult dystrophies which have different age of onset.